Mounting configuration factor for building integrated photovoltaic and retrofitted grid-connected photovoltaic system / Noor Farhana Yusoff ... [et al.]. - Yusoff, Noor Farhana; Zakaria, Nor Zaini; Zainuddin, Hedzlin; Shaari, Sulaiman (2017)
This paper presents the findings of a study to determine the effects of immediate built environment (mounting configuration) on output generated by photovoltaic (PV) module for building integrated photovoltaic (BIPV) and retrofitted PV systems under Malaysian climate. All the systems under study are grid-connected PV (GCPV) system. Eight GCPV systems used in this study; four for BIPV systems and the other four for retrofitted systems. Data for PV module temperature, ambient temperature, plane-of-array solar irradiance and AC power were logged at 5-min interval for all systems. The operating temperature were analysed as the temperature differential with respect to the ambient temperature. The mounting factor was established for both mounting configuration type.